Efek Toksisitas Subakut Ekstrak Etanolik Daun Jambu Biji (Psidium guajava) pada Lambung Tikus Wistar - Esti Dyah Utami; Hanif Nasiatul Baroroh; Nuryanti Nuryanti (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
Psidium guajava leaves have been proven be antiallergic. From the results of previous research, the ethanol extract of leaves is included in the class materials "Practically Non-Toxic." However, repeated administration may cause toxic effects on body organs, one of which was gaster. Subchronic toxicity had been carried out on 20 male Wistar rats and 20 female wistar albino rats. The test materials were administered orally, every day for 28 days. There are 3 (three) doses of test materials which were 250 mg, 500 mg, and 750 mg/kg BW. Observation of the general toxic effect was performed everyday, then organ sampling was performed on day 29 to examined gaster histology and score using Barthel-Manja methods. The result showed that administration of Psidium guajava leaves extract for 28 days caused physical and behavioral changes, caused soft and mucous feces, and also respiratory disorder. But the extract at dose 250 mg, 500 mg and 750 mg/kg BW did not caused changes on gaster histology profile and score. In conclusion, the extract did not have subchronic toxicity effect on gaster rat, but might caused general toxic effect in the higher dose.